2011
DOI: 10.1029/2010jb007909
|View full text |Cite
|
Sign up to set email alerts
|

Magma, faults, and gravitational loading at Mount Etna: The 2002–2003 eruptive period

Abstract: [1] Mount Etna is characterized by a complex structural setting that influences its evolution. In order to understand how the interaction between dike-forming intrusions and faulting influences the kinematics of the volcanic edifice, we developed a numerical model. It takes account of the topography, the medium heterogeneities, the gravitational loading, and the most active crustal discontinuities. A parameterization of the apparent coefficient of friction, as a function of the depth, has been considered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 98 publications
(246 reference statements)
6
34
0
Order By: Relevance
“…Our modeling of the geodetic velocity field has allowed us to precisely pinpoint an area of clockwise rotation rates (Figure 7), which extends in the eastern flank, bounded approximately to the North by the North‐East Rift and the Pernicana fault system, to the North‐East by the Ripe della Naca fault scarps and to the East by the Timpe fault system. This feature is compatible with the area of clockwise rotation found by Solaro et al [2010] and with left‐lateral components revealed along the Pernicana fault system [ Azzaro , 1997, 2004; Aloisi et al , 2011b]. It is also interesting to note the good agreement between the area affected by higher seismic energy release and higher geodetic shear strain values, mainly during the inflation phases.…”
Section: Discussion and Conclusive Remarkssupporting
confidence: 85%
See 1 more Smart Citation
“…Our modeling of the geodetic velocity field has allowed us to precisely pinpoint an area of clockwise rotation rates (Figure 7), which extends in the eastern flank, bounded approximately to the North by the North‐East Rift and the Pernicana fault system, to the North‐East by the Ripe della Naca fault scarps and to the East by the Timpe fault system. This feature is compatible with the area of clockwise rotation found by Solaro et al [2010] and with left‐lateral components revealed along the Pernicana fault system [ Azzaro , 1997, 2004; Aloisi et al , 2011b]. It is also interesting to note the good agreement between the area affected by higher seismic energy release and higher geodetic shear strain values, mainly during the inflation phases.…”
Section: Discussion and Conclusive Remarkssupporting
confidence: 85%
“…We used the entire CGPS network except the stations ECAN, ECNV and EPMN (Figure 1), which are located far outside the volcano edifice and that show a deformation pattern not directly linked to the volcanic dynamics but to a more broad scale tectonic deformation. Moreover, the lower eastern flank of the volcano is affected by an ESE‐ward motion whose origin is still controversial and, as mentioned in the previous paragraph, is not always directly or simply correlated to the magmatic dynamics (for a summary, see sections 6 and 7 in Aloisi et al [2011b] and reference therein). Therefore, for this modeling aimed at imaging the pressure magmatic sources exclusively, we did not take the GPS stations located on the lower eastern flank of the volcano (ELAC, ELEO, EPOZ and ESAL; Figure 1) into account.…”
Section: Analytical Models Of the Cgps Data Recorded During The Inflamentioning
confidence: 99%
“…The results of the two sets of experiments during nonintrusive periods (Figures and a, at t = 2 and 14 min, and Figures and b, at t = 18, 24, and 30 min) show no deformation within the sand ridge (e.g., listric fault formation [ Le Corvec and Walter , ]) suggesting that gravitational loading has no influence on the deformation of our model. The deep flat décollement surface being a first‐order approximation is not consistent with nature; however, as previous studies show, the décollement configuration might be more complex [ Borgia , ], possibly dipping eastward [ Palano et al ., ; Puglisi et al ., ; Aloisi et al ., ] or including more than one décollement [ Tibaldi and Groppelli , ]. The observed deformation during the nonintrusive period of our experiments is principally controlled by tectonic faulting, while the décollement surface enables the flank's lateral movement during intrusive periods accordingly to the similar results of Le Corvec and Walter [] and Walter et al .…”
Section: Discussionsupporting
confidence: 83%
“…As well known in literature (e.g., Cattin et al, 1999;Masterlark 2003;Aloisi et al, 2011;Hsu et al, 2011), the simple analytical model approach (homogeneous, isotropic, Poisson-solid half-space assumption) has in fact strong limitations and introduces significant displacement prediction errors (with respect to measurement uncertainties). In particular, Cattin et al (1999) found that rigidity contrasts, existing within the upper crust can increase the horizontal displacements for a given slip model by up to 40%.…”
Section: Introductionmentioning
confidence: 99%